2003
DOI: 10.1093/jaoac/86.2.412
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Easy Multiresidue Method Employing Acetonitrile Extraction/Partitioning and “Dispersive Solid-Phase Extraction” for the Determination of Pesticide Residues in Produce

Abstract: A simple, fast, and inexpensive method for the determination of pesticide residues in fruits and vegetables is introduced. The procedure involves initial single-phase extraction of 10 g sample with 10 mL acetonitrile, followed by liquid–liquid partitioning formed by addition of 4 g anhydrous MgSO4 plus 1 g NaCl. Removal of residual water and cleanup are performed simultaneously by using a rapid procedure called dispersive solid-phase extraction (dispersive-SPE), in which 150 mg anhydrous MgSO4 and 25 mg primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
2,058
3
118

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 4,685 publications
(2,188 citation statements)
references
References 4 publications
9
2,058
3
118
Order By: Relevance
“…QuEChERS is an acronym for Quick, Easy, Cheap, Effective, Rugged, and Safe. [4,5] This method is used to extract pesticides from food. To prepare an extract, 10 g of homogenized sample was placed in a 50-mL tube and 10 mL of 1% acetic acid in acetonitrile were added.…”
Section: Modified Quechers Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…QuEChERS is an acronym for Quick, Easy, Cheap, Effective, Rugged, and Safe. [4,5] This method is used to extract pesticides from food. To prepare an extract, 10 g of homogenized sample was placed in a 50-mL tube and 10 mL of 1% acetic acid in acetonitrile were added.…”
Section: Modified Quechers Methodsmentioning
confidence: 99%
“…[3] All these techniques frequently require that the entire commodity is composited and then extracted using some variation of the QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) method. [4,5] In the interest of streamlining the sampling and analysis of imported produce for pesticides, a rapid sampling technique has been developed that uses foam swabs to directly sample from the surface of the commodity. The foam swab is then analyzed using a direct analysis in real time (DART) ionization source coupled to an Exactive Orbitrap TM mass spectrometer.…”
mentioning
confidence: 99%
“…The QuEChERS (quick, easy, cheap, effective, rugged, and safe) method is a popular sample extraction method for LC-MS analysis. 27 However, low recovery was reported when QuEChERS was used to extract the high polarity analyte metformin from sample matrices. 28 Because of the high affinity of metformin for the aqueous phase, it could not be completely transferred to the acetonitrile phase during salt-induced phase separation.…”
Section: Stabilitymentioning
confidence: 99%
“…In 2003, Anastassiades et al [5] developed a quick, easy, cheap, effective, rugged and safe (QuEChERS) method aimed at overcoming critical flaws and practical limitations of existing methods. In a follow-up study, Lehotay et al [6] demonstrated its effectiveness for >200 pesticides in lettuce, oranges, and several other matrixes using gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) for analysis.…”
Section: Introductionmentioning
confidence: 99%